Plutarcho Aleksandras: interpretacijos problemos - Juchnevičienė, Nijolė (Literatūra, 2010)
Alexander‘ s character and his activities occupy a special position in the works of Plutarch. Alexander’s Life is the second largest life in the corpus, there are two elaborated speeches on him included intoMoralia, and he is often mentioned in the other pieces of this corpus. The speeches, usually called De Alexandri Magni fortuna aut virtute (A and B), were written by the young Plutarch. They belong to the epideictic rhetoric tradition and are based on the opposition between the hero’s ἀρετήand τύχη, which was in general not favorable to him. According to Plutarch, all Alexander’s life was a struggle between τύχη and ἀρετή. The speeches reveal the impressive portrait of Alexander not only as an invincible warrior, but also as a philosopher in arms, whose immortal achievements are the best proof of his ἀρετή. He managed to overcome the unfavorable τύχη and to civilize the world of the barbarians. There is a difference of interpretation of the character between the speeches and the Life. Alexander is not as perfect there as in the speeches, but his character still is in the center of the narration. The motive of ἀρετήvs. τύχη is also present and Plutarch still sticks to his earlier opinion that Alexander’s ἀρετή, not τύχη was the decisive factor in his life. Plutarch notices the changes in Alexander and his negative features, but at the same time, he tries to explain and extenuate his behavior pointing out to Alexander’s extreme valuation of his δόξα, which he regarded more important than the royal power and the life itself. In my opinion, Alexander’s attitude to his δόξα reveals the difference between the heroes of the pair, Alexander and Caesar. This difference is also expanded in the detailed description of the post-mortal status and fate of their bodies, the effect that reminiscence of them makes on the living. I agree with the opinion, that Caesar is portrayed as a tyrant, who after achieving his egotistic goals was destroyed by the very powers that had helped to achieve it. Caesar in the Plutarch’s lifebelongs to the realm of tragedy. Plutarch’s Alexander belongs to different stylistic vein, that of the heroic epos.